Attitudes Towards Inclusive Education in Teachers and Future Teachers: A Literature Review of Three Instruments - Vega Gonzales, Emilio Oswaldo (2023)
The way of measuring the attitudes towards inclusive education that teachers and future teachers have is not uniform since there are various instruments to carry out this procedure, within which 3 scales present the most appropriate psychometric properties: MATIES, SACIE-R and TAIS. The objective of the study is to synthesize and compare the findings of scientific publications worldwide in the last five years, regarding the attitudes of teachers and future teachers towards inclusive education, considering the aforementioned instruments. The research is framed within the qualitative approach with a narrative review design, which included 23 original articles from indexed journals published between January 2018 and July 2022, identified in the Google Scholar search engine. The results highlight the more frequent use of the SACIE-R, especially in Spain due to its lower number of items, while the MATIES is the one that best analyzes the cognitive, affective and behavioral dimensions of attitudes. In addition, differences were found between the attitudes according to the characteristics of the teachers, being more favorable in those who are dedicated exclusively to special education, those who have fewer years of experience and those who perceive they have been more trained in matters of educational inclusion. It is concluded that the MATIES, SACIE-R and TAIS are valid and useful tools to measure the attitudes of teachers regarding inclusive education.